2023
DOI: 10.1101/2023.04.03.23287498
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal Analysis of Humoral and Cellular Immune Response Following SARS-CoV-2 Vaccination Supports Utilizing Point-Of-Care Tests to Enhance COVID-19 Booster Uptake

Abstract: Individuals with weaker neutralizing responses show reduced protection with SARS-CoV-2 variants. Booster vaccines are recommended for vaccinated individuals, but the uptake is low. We present the feasibility of utilizing point-of-care tests (POCT) to support evidence-based decision-making around COVID-19 booster vaccinations. Using infectious virus neutralization, ACE2 blocking, spike binding, and TCR sequencing assays, we investigated the dynamics of changes in the breadth and depth of blood and salivary anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…All participants had detectable antibody responses 25 months after the 1 st vaccine dose and 15 months after the booster (3 rd ) dose, which is in line with our previous study 12 . Our findings confirm the kinetic pattern of IgG and IgA surges following subsequent immunizations, which restore and increase humoral responses, previously observed 9,[30][31][32] . It also aligns with a few studies that have reported a non-constant decelerating waning of antibodies after COVID-19 vaccination and SARS-CoV-2 infection 8,33,34 , which results in a biphasic decline with an initial rapid decay during the first few months, followed by a phase of slower decline and stabilization.…”
Section: Discussionsupporting
confidence: 91%
“…All participants had detectable antibody responses 25 months after the 1 st vaccine dose and 15 months after the booster (3 rd ) dose, which is in line with our previous study 12 . Our findings confirm the kinetic pattern of IgG and IgA surges following subsequent immunizations, which restore and increase humoral responses, previously observed 9,[30][31][32] . It also aligns with a few studies that have reported a non-constant decelerating waning of antibodies after COVID-19 vaccination and SARS-CoV-2 infection 8,33,34 , which results in a biphasic decline with an initial rapid decay during the first few months, followed by a phase of slower decline and stabilization.…”
Section: Discussionsupporting
confidence: 91%
“…From a clinical standpoint, threshold values of spike- and nucleocapsid-specific IgG and/or SIgA in mucosal sites may serve as more specific and accessible indicators of immunity compared to immunoglobulins found in serum/plasma, potentially influencing decisions about the need for booster vaccinations in high-risk and vulnerable populations ( 17 , 18 ). From the vantage point of vaccine research, an outsized role for SIgA in immunity to SARS-CoV-2 would justify investments in intranasal vaccine platforms designed to target mucosal-associated lymphoid tissues and stimulate local humoral (and cellular) responses ( 4 , 19 ).…”
Section: Assessing Immunity To Sars-cov-2 In Ofmentioning
confidence: 99%